Multiple myeloma risk variant at 7p15.3 creates an IRF4-binding site and interferes with CDCA7L expression - Li, Lily; Johnson, David C.; Weinhold, Niels; Studd, James B.; Orlando, Giulia; Mirabella, Fabio; Mitchell, Jonathan S.; Meissner, Tobias; Kaiser, Martin; Goldschmidt, Hartmut; Hemminki, Kari; Morgan, Gareth J.; et al. (Nature Communications, 2016)
Genome-wide association studies have identified several risk loci for multiple myeloma (MM); however, the mechanisms by which they influence MM are unknown. Here by using genetic association data and functional characterization, we demonstrate that rs4487645 G>T, the most highly associated variant (P = 5.30 × 10−25), resides in an enhancer element 47 kb upstream of the transcription start site of c-Myc-interacting CDCA7L. The G-risk allele, associated with increased CDCA7L expression (P=1.95 × 10−36), increases IRF4 binding and the enhancer interacts with the CDCA7L promoter. We show that suppression of CDCA7L limits MM proliferation through apoptosis, and increased CDCA7L expression is associated with adverse patient survival. These findings implicate IRF4-mediated CDCA7L expression in MM biology and indicate how germline variation might confer susceptibility to MM.